Exposure-based Cash-Flow-at-Risk under Macroeconomic Uncertainty - Niclas Andrén; Håkan Jankensgård; Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 2005)
In this paper we derive an exposure-based measure of Cash-Flow-at-Risk (CFaR). Existing approaches to calculating CFaR either only focus on cash flow conditional on market changes or neglect market-risk exposures entirely. We argue here that an essential first step in a risk-management program is to quantify cash-flow exposure to macroeconomic and market risk. This is the information relevant for corporate hedging. However, it is the total level of cash flow in relation to the firms capital needs that is the information relevant for decision-making. The firms overall CFaR is then calculated based on an assessment of corporate risk exposure.
Keywords: F23; G30; G32; M21; 330; Cash-Flow-at Risk; Corporate Hedging; Downside Risk; Risk Exposure; MUST-analysis; Value-at-Risk; Cash Flow; Risikomanagement; Risikomaß